Evaluation of rock slope stability using field, laboratory, and numerical methods: A case study of critical road sections from Morka- Chencha, in Southern Ethiopia - Hayat Abdela; Bayisa Regassa; Tola Garo; Addisu Bekele (Quaternary Science Advances)
Slope failure is one of the most common geo-environmental natural hazards on steep and mountainous terrain the worldwide resulting in human loss and damage to civil engineering infrastructure. In Southern Ethiopia the road connecting Morka Gircha, and Chencha passes through steep hillside mountains and deep valleys. As a part of this study, slope stability along selected road sections was determined and evaluated, and remedial solutions were provided on the basis of field investigations and numerical analysis. For this study, field research included discontinuity surveys, in situ rock testing, rock sampling for laboratory analysis, slope geometry, and orientation measurements. Field observations revealed that four crucial rock slope sections were selected for stability analysis assessment. Kinematic assessments via Dips software at slope sections RS2 and RS4 revealed the planar kinds of rock slope failure. Further stability analysis via the RocPlane program revealed that the crucial rock slope sections at RS2 are unstable under all anticipated conditions. However, the rock critical slope segment at RS4 remains stable under static dry, dynamic dry, and static saturated conditions and unstable under dynamic saturated conditions. Furthermore, a stability study was conducted via limit equilibrium and finite element methods for static dry, static saturated, dynamic dry, and dynamic saturated loading scenarios at crucial rock slope sections RS1 and RS5. This study's performance analysis of geometric profiles indicates that variations of slope height and slope angle lead to greater slope stability. This shows that the factor of safety values in both the LEM and FEM change as the slope angle and slope height decrease. Furthermore, the study reveals that the insertion of rock bolts at planar failure sites increases the FOS slope.